Enhanced Removal of Mercury and Lead by a Novel and Efficient Surface-Functionalized Imogolite with Nanoscale Zero-Valent Iron Material - Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K; Maldonado-Hernandez, T; Maldonado-Hernandez, T; Flores-Salinas, C; Flores-Salinas, C (Springer Science and Business Media Deutschland GmbH, 2022)
A novel hybrid nanomaterial, nanoscale zero-valent iron (nZVI)-grafted imogolite nanotubes (Imo), was synthesized via a fast and straightforward chemical procedure. The as-obtained nanomaterial (Imo-nZVI) was characterized using transmission electron microscopy (TEM), electrophoretic mobility (EM), and vibrating sample magnetometry (VSM). The prepared Imo-nZVI was superparamagnetic at room temperature and could be easily separated by an external magnetic field. Sorption batch experiments were performed for single- and multicomponent systems and demonstrated that Hg2+ and Pb2+ could be quantitatively adsorbed at pH 3.0. For multicomponent systems, maximum adsorption capacities of 61.6 mg·g−1 and 76.9 mg·g−1 were obtained for Hg2+ and Pb2+ respectively. It was observed that the functional groups in Imo-nZVI interact preferentially with analytes according to the Misono softness parameter. The higher performance of Imo-nZVI compared with Imo and nZVI is related to the increased number of adsorption sites in the functionalized nanomaterial. The sorption equilibrium data obeyed the Langmuir model, while kinetic studies demonstrated that the sorption processes of Hg2+ and Pb2+ followed the pseudo-second-order model. This study suggests that the Imo-nZVI composite can be used as a promising sorbent to provide a simple and fast separation method to remove Hg and Pb ions from contaminated water. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.